OPTIMALIASASI PERAN KADER DALAM DETEKSI DINI KANKER SERVIKS - Novia - Nuraini; Yudhia Fratidina; siti masitoh (IFI cabang Kota Bekasi, 2023)
The cervix is a female organ that connects the vagina and uterus. Cervical cancer is a malignant tumor that grows in the cervix, can originate from cells of the cervix or both. This cancer is one of the reproductive disorders most feared by women. In Indonesia, the second type of cancer is 32,469 cases or 9.3% of the total cancer cases. Early detection of cervical cancer with an IVA (Visual Infection with Acetic Acid) test needs to be carried out routinely by women at least once a year for women who are sexually active. Community service is a way to increase public knowledge and awareness about how to detect early women's reproductive health. The method used in community service is by holding training on cervical ca knowledge and training cadre communication to ensure the community routinely detects early women's reproductive health, conducting interviews, FGDs, observing IVA Tests. The results obtained from community service, community knowledge increased to 98%, behavior with IVA Test participants in the cadre area increased by 50%, cadres also actively provided re-education with communication during training at events that were often held in their place, such as recitations, Posyandu is also a social gathering for mothers. During the IVA test observation, one person was found to be positive. IVA test every month or Pap smear every year